Epibenthic assemblages of hard-substrate habitats in the German Bight (south-eastern North Sea) described using drift videos. (1st March 2019) - Michaelis, Rune; Hass, H. Christian; Mielck, Finn; Papenmeier, Svenja; Sander, Lasse; Gutow, Lars; Wiltshire, Karen H.
Abstract: Globally, marine subtidal hard-substrate habitats provide important ecological functions to a variety of sessile and mobile taxa. The southern North Sea is a marine environment with relatively low amounts of hard-substrate areas. Surveys with high taxonomic resolution on the associated hard-substrate epifauna, e.g. by diving observations, are challenging in this region because of strong tidal currents and considerable water depths. Therefore, the characteristics and functions of hard-substrate habitats in the North Sea remain poorly understood. The goal of this study was to extend the knowledge on sessile taxa assemblages in four hard-substrate areas within the German Bight (SE North Sea) using underwater video observations as a straight-forward and visual method to obtain and process detailed data on seafloor characteristics. Still images from drift videos were analyzed to determine the epifaunal assemblages attached to the stones on a presence/absence scale. A subsample of cobbles, boulders and large boulders was further investigated to derive quantitative data on the colonized area for each taxon and stone size. The four areas showed significant differences in sessile taxa richness, with higher numbers of sessile taxa in the deeper far-shore areas than in the shallower nearshore areas, despite a generally high similarity in the sessile animal taxa spectrum. Within the areas, cobbles were mainly dominated by short-lived taxa (<5 years) like Spirobranchus triqueter and ascidians, while boulder-sized stones were largely colonized by long-lived taxa (>5 years) like Metridium dianthus, Flustra foliacea and Alcyonium digitatum . Most of the stones were typically covered by epifauna by more than 50%. The differences in the sessile taxa spectrum between the areas were interpreted as a consequence of reduced abiotic stress and higher habitat complexity in the far-shore areas. The dominance of short-lived taxa on cobbles, in comparison to long-lived taxa on boulder-sized stones, possibly reflects the frequency of disturbance and the competitiveness of these taxa. Highlights: Taxa richness is higher in far-shore areas than in nearshore areas. When colonized, stones are typically covered by sessile organisms to more than 50%. Sessile assemblages on boulder-sized stones are dominated by long-lived taxa. Dominance of short-lived taxa on cobbles are indicative of regular disturbances.